Karakteristik Kepala Daerah Dan Audit Delay Laporan Keuangan Pemerintah Daerah Di Indonesia - Hesy Erlisa Frasti; Elvanya Purba Dita; Euodia Pracinthea; Ade Syahputra; Arini Widyawati; Santoso Tri Hananto (Jurnal Akuntansi, 2017)
This study aimed to examinethe effectsof regent/ mayor characteristics onfinancial statement of local government’s audit delay in Indonesia. Regional head arecharacterized by age, educational background, executive work experience, andeducational level. The populationof this study were all of districts/municipalitie inIndonesia. This study uses 142 districts/municipalities as sample usingpurposivesampling method. The secondary data was obtained from Audit Board of the Republicof Indonesia (BPK-RI) and Ministry of Home Affairs of the Republic of Indonesia(Kemendagri). Datawas analyzed using regression model. The analysisshowed thatthe economics or accounting educational background has negatively affected onfinancial statement of local government’s audit delay in Indonesia. However, age,executive work experience, and education level do not affect financial statement oflocal government’s audit delay in Indonesia.